2014
DOI: 10.1002/jor.22722
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic differences in human cartilage between mild and severe OA

Abstract: The development of osteoarthritis (OA) depends on genetic and environmental factors, which influence the biology of the chondrocyte via epigenetic regulation. Changes within the epigenome might lead the way to discovery of new pathogenetic pathways. We performed a genome-wide methylation screening to identify potential differences between paired mild and severe osteoarthritic human cartilage. Sixteen female patients suffering from OA underwent total knee joint replacement. Cartilage specimens collected from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…In some of these studies, differences among sample groups were most pronounced in genes involved in inflammation and immune-responses [12, 14], while others reported an over-representation of genes involved in developmental pathways [15, 16]. These studies corroborated previous findings for some identifiable genes associated with the onset and progression of OA.…”
Section: Introductionsupporting
confidence: 77%
“…In some of these studies, differences among sample groups were most pronounced in genes involved in inflammation and immune-responses [12, 14], while others reported an over-representation of genes involved in developmental pathways [15, 16]. These studies corroborated previous findings for some identifiable genes associated with the onset and progression of OA.…”
Section: Introductionsupporting
confidence: 77%
“…83 In another study, 1,214 differentially methylated genetic targets were identified in a comparison of paired samples of knee cartilage showing mild or severe OA. 84 A number of the identified genes were related to devel opmental and celldifferentiation pathways, supporting the proposed involvement of these mechanisms in OA. A more hypothesisdriven approach was used to demon strate that methylation of the SOX9 promoter is increased in OA, compared with normal cartilage.…”
Section: Inflammation In Oamentioning
confidence: 71%
“…Genome-wide DNA methylation studies have identified epigenomic changes in OA cartilage (54) along with differences between mild and severe OA (55), different epigenomic landscapes in hip and knee cartilage (56) and distinct clusters of OA patients (57, 58). Numerous studies have revealed the importance of DNA methylation in controlling the expression of OA-related genes, including Phlpp1 (59), IL8 (60), and genes encoding proteinases, including MMPs and ADAMTSs (28, 53, 61).…”
Section: Discussionmentioning
confidence: 99%